Difficult diagnosis of a neurogenic thoracic outlet syndrome and review of the current literature - Rosa, Joao Maia; Sousa, Arnaldo; Fonte, Helder; Pereira, Eva; Sapage, Rita; Trigueiros, Miguel (International Journal of Research in Orthopaedics, 2020)
Thoracic outlet syndrome (TOS) is an uncommon disorder, without a clear clinical presentation or a fully accepted definition. The patients usually present a set of symptoms arising from compression of the brachial plexus or subclavian vessels during their passage through the thorax, between the base of the cervical region and the axilla. The authors present a case of a 20 years old woman with sporadic paresthesia in the territory of C7-T1 nerve root. At the physical examination she had a positive Wright's test. The imaging studies revealed the presence of a right cervical rib. A partial rib resection was performed with exploration of the braquial plexus and at the current follow up; 24 months after the surgery, the patient is asymptomatic. Our objective is to present a case of TOS and to highlight the clinical-management and treatment challenges of this pathology.